Designing graded catalytic domain to homogenize temperature distribution while dry reforming of CH4. (6th September 2018) - Aydın, Özgür; Kubota, Atsushi; Tran, Dang Long; Sakamoto, Mio; Shiratori, Yusuke
Abstract: While utilizing biogas in Solid Oxide Fuel Cell (SOFC) systems equipped with either internal or external catalytic domain possessing a uniform catalytic activity, the rate of the reforming reaction significantly changes along the flow field due to the rapid conversion of the methane in the inlet region. Thus, a dramatic temperature variation develops along the flow field, resulting in thermal stress on the adjacent components. To mitigate the temperature variation, design of a catalytic domain graded in terms of the catalyst loading along the flow field is a promising solution, for which herein we present a strategy based on numerical modeling and in situ temperature measurement along the reformer. We design a graded catalytic domain for a uniform temperature distribution and demonstrate it experimentally, aiming the efficient use of biogas in SOFC systems. Highlights: Design strategy for grading catalytic domain for dry CH4 reforming in a reformer. Uniform temperature profile during dry CH4 reforming by graded catalytic domain. Longitudinally controlled dry CH4 reforming rate for a uniform temperature profile. Spatially measured interior/surface temperature of reformer while dry reforming of CH4 .